2020
DOI: 10.2478/atd-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

Educational Use of Social Media in Higher Education: Gender and Social Networking Sites as the Predictors of Consuming, Creating, and Sharing Content

Abstract: Introduction:This study investigates the influence of gender and social networking sites (SNSs) such as Instagram, YouTube, WhatsApp, Facebook, and Twitter on consuming, creating, and sharing content within the educational social media usage behaviors of higher education students. The survey method is applied to measure students’ social media usage for educational purposes. So that a more effective use of social media in education can be provided, it is important to understand how university students vary in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…Considering the user behaviours in the digital communication dimension, it was seen that the majority of participants had a good level of knowledge. This study confirms current researches (Torun, 2020) that students use digital communication channels and social media tools to a large extent and follow the developments. The participants on the whole stated that they preferred digital communication methods for reasons such as "saving time and cost, communicating quickly and facilitating accessibility".…”
Section: Discussionsupporting
confidence: 90%
“…Considering the user behaviours in the digital communication dimension, it was seen that the majority of participants had a good level of knowledge. This study confirms current researches (Torun, 2020) that students use digital communication channels and social media tools to a large extent and follow the developments. The participants on the whole stated that they preferred digital communication methods for reasons such as "saving time and cost, communicating quickly and facilitating accessibility".…”
Section: Discussionsupporting
confidence: 90%
“…We used basic and recommended indicators to test the suitability of the verified model. The basic recommended evaluation indicators [28] and their real achieved values on the applied four-factor model are given in Table 6. The model applied in the research part is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…To solve this problem, there have been several studies on the educational use of SNS, which is a representative of LL. However, the samples of these studies included students receiving higher education ( Akçayir 2017 ; Torun 2019 , 2020 ). As such, our finding that elementary school female students had a positive attitude toward LL is noteworthy in that it suggests a way to solve the gender gap in the technology sector.…”
Section: Discussionmentioning
confidence: 99%